Tafsir Pendidikan Perempuan Menurut Qasim Amin - Elya Munfarida (MAGHZA, 2020)
The encounter between Arab Islam and colonialism and modernity resulted in a revival of Arab Islamic intellectuals with an orientation to reinterpret the Islamic tradition. Qasim Amin as one of the Nahdah figures tries to reinterpret Islamic teachings and traditions, especially those related to women, by accommodating modern ideas and culture. Based on his criticism of the reality of the restriction and subordination of women in the public sphere, Amin tries to reinterpret women's education in Egypt by re-exploring the texts of the Koran and hadiths that talk about women's rights and obligations, the interpretations of the scholars of the two texts, the values ​​and basic principles of Islamic shari'ah that underlie Islamic legislation, as well as sociological theories and liberal feminist thinking. According to Amin, women's education is very significant with three interests, namely society in the form of participation in various fields in the public sphere, the family in the form of the ability to be able to better protect their children, and the state in the form of producing offspring with good intellectual and moral qualities that have an impact on the progress of the country. The realm of education that must be accessed by women includes intellectual, moral, and physical education.